NIMG-45. DIFFUSION MRI AS AN EARLY BIOMARKER OF OVERALL SURVIVAL BENEFIT IN RECURRENT GLIOBLASTOMA TREATED WITH IMMUNE CHECKPOINT INHIBITORS. (12th November 2021) - Hagiwara, Akifumi; Jingwen, Yao; Oughourlian, Talia; Wang, Chencai; Raymond, Catalina; Everson, Richard; Patel, Kunal; Mareninov, Sergey; Yong, William; Salamon, Noriko; Pope, Whitney; Nghiemphu, Phioanh; et al.
Abstract: Diffusion magnetic resonance imaging (MRI) estimates of the apparent diffusion coefficient (ADC) has been revealed to be useful for predicting treatment response in patients with glioblastoma (GBM), with an increase in ADC indicating tumor cell death. The aim of the current study was to investigate whether quantitative changes in diffusion MRI after treatment with immune checkpoint inhibitors (ICI) could predict OS in patients with recurrent GBM. A total of 61 patients were included in this retrospective study with the following inclusion criteria: (i) diagnosis of recurrent GBM treated either with pembrolizumab or nivolumab and (ii) availability of diffusion data in pre- and post-ICI MRI. Tumor volume and median relative apparent diffusion coefficient (rADC) within enhancing tumor with respect to normal-appearing white matter were calculated. Median OS for all patients was 7.6 months (range, 1.0–30.6 months). Results showed that higher post-treatment rADC was associated with significantly longer OS (median, 372 days for rADC ≧ 1.42 versus 211 days for rADC < 1.42; P = 0.01, log-rank test), whereas tumor volume and pre-treatment rADC were not significantly associated with OS. Cox regression analysis revealed post-treatment rADC significantly influences OS (P = 0.02, univariate analysis), even after controlling for age, sex, and IDH status (P = 0.007, multivariate analysis), and additionally controlling for whether surgery was performed after ICI treatment (P = 0.049, multivariate analysis). In conclusion, a high post-treatment rADC may be an early imaging biomarker for identifying OS benefit in recurrent GBM patients receiving ICI treatment.